Farmer participatory development of a control strategy for the variegated grasshopper with a biopesticide in the northern Mono, Benin. - Muller, D.; Gbongboui, C.; Groote, H. de; Langewald, J.; Badou, R. (2000)
Farmers of two villages in Mono province, Benin, in collaboration with researchers of the biological control of locusts and grasshoppers program (LUBILOSA) at IITA, developed a use and marketing strategy for the biopesticide Green Muscle, an oil-based formulation of the entomopathogenic fungus Metarhizium anisopliae var. acridum for the control of Zonocerus variegatus L. Three different doses, two different sprayers and two different periods of control were tested. Farmers preferred the preventive treatment with a medium dose (20 g/ha) by ULV spinning disk sprayer. Half a day of training for a village brigade was found to sufficient to enable them to identify the egg laying areas and to apply the biopesticide. Farmers would prefer the producer to sell the biopesticide on credit, directly to the village association. The village brigade will treat the grasshoppers, and be reimbursed by the concerned farmers.